1996
DOI: 10.1139/v96-131
|View full text |Cite
|
Sign up to set email alerts
|

Topological analysis of the experimental electron density

Abstract: Abstract:Methods of topological analysis of the experimental electron density reconstructed from X-ray diffraction data are described. Their advantages and drawbacks are discussed and the results for organic and inorganic crystalline solids are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…This is most pronounced for the covalent interactions, which are worst described by the rigid-atom model usually used for X-ray diffraction refinement. However, comparative topological studies of the theoretical and experimental charge densities of the compounds displaying shared interactions (Abramov & Okamura, 1996;Tsirelson, 1996) revealed that atomic thermal-motion effects are not crucial for the possibility of quantitative and semiquantitative evaluation of the respective charge density and its Laplacian at the bond critical point from a highly accurate X-ray diffraction experiment. Such accuracy does not seem to be limiting for the semiquantitative evaluation of the local kinetic energy at the bond critical point of the accurate experimental charge density by the suggested method.…”
Section: Some Experimental Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most pronounced for the covalent interactions, which are worst described by the rigid-atom model usually used for X-ray diffraction refinement. However, comparative topological studies of the theoretical and experimental charge densities of the compounds displaying shared interactions (Abramov & Okamura, 1996;Tsirelson, 1996) revealed that atomic thermal-motion effects are not crucial for the possibility of quantitative and semiquantitative evaluation of the respective charge density and its Laplacian at the bond critical point from a highly accurate X-ray diffraction experiment. Such accuracy does not seem to be limiting for the semiquantitative evaluation of the local kinetic energy at the bond critical point of the accurate experimental charge density by the suggested method.…”
Section: Some Experimental Results and Discussionmentioning
confidence: 99%
“…The latter field of application is now rapidly developing (e.g. Kapphann, Tsirelson & Ozerov, 1988;Craven & Stewart, 1990;Destro, Bianchi, Gatti & Merati, 1991;Gatti, Bianchi, Destro & Merati, 1992;Destro & Merati, 1995;Iversen, Larsen, Souhassou & Takata, 1995;Tsirelson, 1996;Tsirelson & Ozerov, 1996) owing to the possibility of analytical representation of the experimental electron density by various multipole models (Hirshfeld, 1971;Stewart, 1976;Hansen & Coppens, 1978), which allow analytical or numerical evaluation of the total electrondensity Laplacian and gradient vector field. In the present work, an attempt to develop an approach for the evaluation of electronic kinetic energy density at the bond critical-point region from the experimental electron density is described.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, the only way to evaluate indirectly to what extent quantitative values of topological characteristics depend on the atomic thermal motion effects may be a comparative topological analysis of theoretical and experimental charge densities simultaneously. Previously, such studies of L-alanine (Gatti, Bianchi, Destro & Merati, 1992) and urea (Tsirelson, 1996, and references therein) crystals have revealed quantitative, within 5%, and semiquantitative, within 10-20% (or even qualitative, within 60%), agreement between theoretically and experimentally evaluated values of p and V2p, respectively, at the bond critical points (saddle points of p between bonded atoms) between nonhydrogen atoms. The worst agreement was found between experimental and theoretical values of these properties for C--N and N--O interactions in lithium bis(tetramethylammonium) hexanitrocobaltate(III) (Bianchi, Gatti, Adovasio & Nardelli, 1996).…”
Section: Introductionmentioning
confidence: 88%
“…The field of its application to experimental (X-ray diffraction) charge densities is rapidly developing now (e.g. Kapphahn, Tsirelson & Ozerov, 1988;Craven & Stewart, 1990;Gatti, Bianchi, Destro & Merati, 1992;Destro & Merati, 1995;Iversen, Larsen, Souhassou & Takata, 1995;Tsirelson & Ozerov, 1996) owing to the possibility of analytically representing experimental p by various multipole techniques (Hirshfeld, 1971;Stewart, 1976;Hansen & Coppens, 1978), allowing analytical evaluation of the Laplacian, V2p, and gradient vector field of p. Although it seems that there is no fundamental restriction on the applicability of topological analysis to experimental p (Tsirelson, 1996), the numerical results in this case are affected by the thermal atomic motions in crystals (Tsirelson, 1996;Gatti, Bianchi, Destro & Merati, 1992) and in fact refer to the mean thermal nuclear distribution. In this situation, the only way to evaluate indirectly to what extent quantitative values of topological characteristics depend on the atomic thermal motion effects may be a comparative topological analysis of theoretical and experimental charge densities simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…20 This association was confirmed by further theoretical calculations of the density and, most importantly, by the topological analysis of experimentally measured electron densities. [21][22][23][24] Such calculations 25 and experiments [26][27][28][29] have now provided thousands of examples, demonstrating that every classical structure is but a mapping of the "bonds" onto the network of bond paths. EVery classical structure is mirrored by a molecular graph: the network of bond paths linking neighboring, that is, bonded, nuclei.…”
Section: Relating Structure To the Measurable Electron Densitymentioning
confidence: 99%